SIMULTANEOUS ESTIMATION OF AZILSARTAN AND CILNIDIPINE IN BULK BY RP-HPLC AND ASSESSMENT OF ITS APPLICABILITY IN MARKETED TABLET DOSAGE FORM - ANDHALE, SWATI M.; G. NIKALJE, ANNA PRATIMA (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aims to build up the RP-HPLC process for Azilsartan and Cilnidipine and authenticate the RP-HPLC process according to ICH validation code Q2R1. Methods: System suitability testing was performed to discover the qualifying criterion of the method by injecting the identical standard solution of Azilsartan 40μg/ml and Cilnidipine 10μg/ml in mixture/combination in subsequent optimized chromatographic conditions and the chromatogram was recorded. Moreover, the planned method was validated as per ICH guideline Q2R1 for the following parameters: linearity and range, precision, accuracy, robustness, and determined % recovery. Results: The outcomes of %RSD for retention time and peak area were found to be 0.65 and 1.32 for Azilsartan and 0.85 and 1.90 for Cilnidipine. The correlation coefficient, y-intercept, slope of the regression line were 0.9996,-1127.1, 3313.9, and 0.9993, 1460.2, 2876.4 for Azilsartan and Cilnidipine, respectively. Moreover, the range of this method was observed to be 40-240μg/ml and 10-60 μg/ml for Azilsartan and Cilnidipine, standard concentrations respectively. The % RSD achieved for precision (repeatability) was observed in the range of 1.57 to 2.43 for Azilsartan and 0.70 to 1.88 for Cilnidipine. The % accuracy was found in the range of 96.96 to 101.92% w/w for Azilsartan and 99.19 to101.96%w/w for Cilnidipine. The percent recovery values achieved for Azilsartan were in the range of 99.87 to 106.39% w/w and for Cilnidipine in the range of 94.51 to 105.96% w/w. Conclusion: The author concludes that the simultaneous estimation of Azilsartan and Cilnidipine with predefined objectives was successfully achieved. Moreover, the method was found to be steadfast for the quantification of Azilsartan and Cilnidipine in marketed tablet dosage forms.